China's New Art, Post - 1989 : with a Retrospective from 1979-1989. - Hong Kong City Hall, Hong Kong; Pao Galleries, Hong Kong; Hong Kong Arts Centre, Hong Kong (Hong Kong : Hanart T Z Gallery, 1993)
Wang Guangyi ; Yu Youhan ; Li Shan ; Geng Jianyi ; Wu Shanzhuan ; Ye Yongqing ; Wang Ziwei ; Feng Mengbo ; Hong Hao ; Liu Dahong ; Ren Jian ; Wei Guangqing ; Guan Wei ; Wang Youshen ; Qiu Zhijie ; etc.
China's New Art, Post - 1989 with a Retrospective from 1979-1989, Exhibition Hall, Low Block, Hong Kong City Hall, Central, Hong Kong, 31 January - 14 February 1993 ; Pao Galleries, 4th and 5th Floors, Hong Kong Arts Centre, Hong Kong, 2 February - 25 February 1993
kunstcatalogus
Keywords: China